2021
DOI: 10.20892/j.issn.2095-3941.2020.0313
|View full text |Cite
|
Sign up to set email alerts
|

Protein convertase subtilisin/Kexin type 9 inhibits hepatocellular carcinoma growth by interacting with GSTP1 and suppressing the JNK signaling pathway

Abstract: Objective: Protein convertase subtilisin/Kexin type 9 (PCSK9) has been found to be closely associated with the occurrence and development of numerous tumors. However, the precise role of PCSK9 and its relationship to the development of hepatocellular carcinoma (HCC) remain largely unknown. This study aimed to clarify these issues. Methods: The expression levels of PCSK9 in HCC tissues and HCC cell lines were determined by the quantitative reverse transcription polymerase chain reaction, Western blot, and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Nevertheless, tumor and nontumor tissues seem to differentially regulate PCSK9 expression. In patients, PCSK9 mRNA and protein were lower in HCC tissues compared to adjacent tissues [20,169]. These findings coincided with high LDL-R mRNA and protein levels in HCC tissues compared to adjacent nontumor tissues [20].…”
Section: Pcsk9 and Hcc Progressionmentioning
confidence: 64%
See 2 more Smart Citations
“…Nevertheless, tumor and nontumor tissues seem to differentially regulate PCSK9 expression. In patients, PCSK9 mRNA and protein were lower in HCC tissues compared to adjacent tissues [20,169]. These findings coincided with high LDL-R mRNA and protein levels in HCC tissues compared to adjacent nontumor tissues [20].…”
Section: Pcsk9 and Hcc Progressionmentioning
confidence: 64%
“…This decreased metastatic spread was lost upon feeding with a high-cholesterol diet, overriding genetic alterations that lower the risk for cancer cell spreading [168]. Another report showed PCSK9 to interact with glutathione S-transferase Pi 1 (GSTP1), thereby blocking activation of Jun N-terminal kinase (JNK) and consequently inhibiting HCC growth [169]. Furthermore, HCC patients exhibiting low PCSK9 levels had a shorter overall survival and recurrencefree survival time compared to HCC patients with high amounts of PCSK9 [20,169].…”
Section: Pcsk9 and Hcc Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, current anti-angiogenic clinical trials induce only a modest improvement in OS, measurable in just several months. Given that HCC has multiple pathways for recruiting vessels, blocking one target alone may have incomplete effects on tumor angiogenesis, because the tumor cells may switch from one mechanism to another 132 , 138 . However, the use of anti-angiogenic molecules may lead to a hypoxic TME, which alters the cell phenotype and enhances tumor invasiveness, whereas the tumor-infiltrating cells, including TAMs, TANs, and TAFs, may decrease the response to anti-angiogenic therapies 139 .…”
Section: Anti-angiogenic Therapies In Hcc Angiogenesismentioning
confidence: 99%
“… 46 On the contrary, other studies reported decreased PCSK9 expression in HCC implying that liver tumors can modulate their local and adjacent microenvironment, thus enabling energy supply to fuel tumor growth. 47 A brilliant study demonstrated that deleting PCSK9 gene in rodent cancer cells substantially affects their growth in vivo and, notably, improves the efficacy of anti-programmed cell death protein 1 (PD1) therapy, opening the way towards combined immune checkpoint-based strategies. Mechanisms of action seem independent of the cholesterol regulation, rather relying on the recycling of MHC I molecules for degradation to lysosomes.…”
Section: Genetically Modified Mouse Models Of Nash-hccmentioning
confidence: 99%